2016
DOI: 10.1186/s12887-016-0664-0
|View full text |Cite
|
Sign up to set email alerts
|

Equipment for neonatal resuscitation in a middle-income country: a national survey in Vietnam

Abstract: BackgroundInterventions to improve neonatal resuscitation are considered a priority for reducing neonatal mortality. In addition to training programs for health caregivers, the availability of adequate equipment in all delivery settings is crucial. In this study, we assessed the availability of equipment for neonatal resuscitation in a large sample of delivery rooms in Vietnam, exploring regional differences.MethodsIn 2012, a structured questionnaire on 2011 neonatal resuscitation practice was sent to the head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Similar to our findings, missing or underutilised essential equipment, logistical difficulties and poor supply have been described in lower‐middle‐income countries as barriers to delivering newborn care . Inadequate hygiene measures, documentation, staff knowledge and skills and insufficient essential equipment are common themes .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to our findings, missing or underutilised essential equipment, logistical difficulties and poor supply have been described in lower‐middle‐income countries as barriers to delivering newborn care . Inadequate hygiene measures, documentation, staff knowledge and skills and insufficient essential equipment are common themes .…”
Section: Discussionsupporting
confidence: 88%
“…Similar to our findings, missing or underutilised essential equipment, logistical difficulties and poor supply have been described in lower-middle-income countries as barriers to delivering newborn care. [14][15][16] Inadequate hygiene measures, documentation, staff knowledge and skills and insufficient essential equipment are common themes. [16][17][18][19] In other assessments where essential equipment is available, other systemic factors, such as hand hygiene, inadequately trained staff, poor routine care, documentation and prescribing practices, have an impact the quality of newborn care, 20,21 highlighting the need to focus beyond structural improvements.…”
Section: Discussionmentioning
confidence: 99%
“…[5,15] According to the study conducted by De Graft Johnson et al,(2017) reported that most facilities had some supplies of NR equipment, from a high 90.7% availability of suction devices and 81.9-100% for bag and mask to gaps in basics, such as 40.5% for towels and blankets essential for thermoregulation. [5,24] The availability of NR equipment varied depending on the type of health facility; it was typically higher in hospitals, and lower in health centers.…”
Section: Discussionmentioning
confidence: 99%
“…[2] But in contrast to a survey in Vietnam, whereby 50.3% of the 187 health facilities had clocks. [24] Protocols and guidelines were present for NR, with over half (55.2%) having visual NR action plans and guidelines, and NR flip charts (55.2%) available on the labor and maternity theater units. Though the majority (65.5%) of HCPs did not refer to them during NR intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation